Галлицы (Diptera, Cecidomyiidae) подсемейства Lestremiinae из Крыма - Берест, 3.Л. (Вестник зоологии, 1988)
А review of all 9 species known to occur in the Crimea. Five of them are reported for the first time, one described as new: Peromyia emarginata sp. n. (Т у р е - l о с а I i t у: Crimea, Simferopol region, Krasnolesye). Туре material (holotype male and paratype female) is deposited iп the Schmalhausen Institute of Zoology (Kiev).